Total quality management - Richardson, Terry L. (Albany, N.Y. : Delmar, 1997)
Introduction to change: history lessons in pursuing quality; the challenge of change; world quest for quality. The total quality system: the quality imperative and quest; quality as a philosophy. Steps to implementation of TQM: strategies for total quality management; preparation and planning phases; assessment; implementation phase; networking phase. Implementing quality methods and techniques, group and team problem-solving techniques; quantitative and statistical analysis. Total quality management and planning tools: quality improvement tools; Controlling and improving processes; system improvement techniques. Quality standards.
Keywords: Management; Total quality management